Bibliometric Analysis From 2014-2024: Integration of Ethnoscience in Science Learning - Endah Febri Setiya Rini; Sentot Budi Rahardjo; Bramastia Bramastia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Ethnoscience has become a fairly well-established field among academics, although the topic is still developing. This study aims to analyze research trends related to ethnoscience published in the period 2014 to 2024. Methodology: This study uses bibliometric analysis and systematic literature review. Data collection was carried out by searching for the keyword